Upaya Meningkatkan Kemandirian NU Ranting Wates melalui Kerjasama Kelembagaan antar Ranting Nu di Kecamatan Tanjunganom Kabupaten Nganjuk - Saini, Mukhamat; Mufidah, Luluk Indarinul (Universitas Pangeran Diponegoro Nganjuk, 2023)
The purpose of assisting the NU Branch Wates community is to increase the independence of the NU Branch Wates Village, with the hope that when there is a visitation of the NU Award at the NU, MWCNU and PCNU levels of Nganjuk Regency at least they can enter the selection of at least the top 10. There are several organizations operating in Wates Village, namely youth organizations, PKK, Posyandu, and religious groups including NU, Muhammadiyah, LDII and others. However, most of the religious organizations in Wates Village are from the NU group. Assistance using the ABCD (Asset Based Community and Development) approach, which prioritizes the utilization of existing assets and potential in the Wates Village area which is owned by the NU institutional organization. With the institutional cooperation between the NU branches in Wates Village, it is hoped that the administration of the management will be well organized, the NU branches will be more independent which will later be able to make progress for the community to develop the NU institutions in Wates Village. Based on the mutual agreement, the organization's independent economic cooperation with the management of the NU Branch was ratified through the signing of cooperation from both parties, namely the NU Branch Wates and NU Branch Juwet. Namely, about Organizational Management, Organizational Management, Organizational Independent Economic Activities. The mentoring process to increase the independence of NU through institutional cooperation with NU Ranting Juwet has successes and shortcomings, this success includes being able to help foster independence in NU Ranting Wates to work together with Ranting Juwet in the field of plant nurseries by utilizing existing potential and assets. The positive impact is increasing personal capacity in knowledge and understanding of asat or potential, the nursery process, care and marketing either through social media or partnership.